Prognostic Role of High Sensitivity C-Reactive Protein in Patients With Acute Myocardial Infarction - Zhang, Xiaoyuan; Wang, Shanjie; Fang, Shaohong; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Background: High sensitivity CRP (hs-CRP) has attracted intense interest in risk assessment. We aimed to explore its prognostic value in patients with acute myocardial infarction (AMI). Methods and Results: We enrolled 4504 consecutive AMI patients in this prospective cohort study and used the regression analyses to assess it. Over a median follow-up of 1 year, 1112 (24.7%) patients developed in-hospital HF, 571 (18.9%) patients developed HF post-discharge and 262 (8.2%) patients died. In the fully adjusted model, the risk of in-hospital heart failure (HF) (95% confidence intervals (CI)) among those patients with hs-CRP values in quartile 3 (Q3) and Q4 were 1.36 (1.05 to 1.77) and 1.41 (1.07 to 1.85) times as high as the risk among patients in Q1 (p trend < 0.001). Patients with hs-CRP values in Q3 and Q4 had 1.33 (1.00 to 1.76) and1.80 times (1.37 to 2.36) as high as the risk of HF post-discharge compared with patients in Q1 respectively (p trend<0.001). Patients with hs-CRP values in Q3 and Q4 had 1.74 (1.08 to 2.82) and 2.42 times (1.52 to 3.87) as high as the risk of death compared with patients in Q1 respectively (p trend<0.001). Conclusions: Hs-CRP was found to be associated with the incidence of in-hospital HF, HF post-discharge and all-cause mortality in patients with AMI.